Сombined Calculation of Electric Power Technical Losses in 0,38–10 kV Electrical Networks - M. I. Fursanov; A. A. Zalatoi; V. V. Makarevich; A. I. Kuntsevich (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper presents results of practical calculation for electric power technical losses on the basis of a combined calculation methodology for 0,38–10 kV electrical networks. The results have been evaluated and analyzed in the paper. The paper considers an influence of non-uniform loading of 0.38 kV network phases  on electric power technical losses.